Income, Aspirations and the Hedonic Treadmill in a Poor Society. - Knight, J; Gunatilaka, R (Department of Economics (University of Oxford), 2009)
A specially designed household survey for rural China is used to analyse the determinants of aspirations for income, proxied by reported minimum income need, and the determinants of subjective well-being, both satisfaction with life and satisfaction with income. It is found that aspiration income is a positive function of actual income and reference income, and that subjective well-being is raised by actual income but lowered by aspiration income. These findings suggests the existence of a partial hedonic treadmill, and can help to explain why subjective well-being in China appears not to have risen despite rapid economic growth.